Relationship between anxiety and sleep quality in patients attending Kecamatan Penjaringan Public Health Center, North Jakarta - Micheline Chang; Surilena Hasan; Erfen Gustiawan Suwangto; Nelly Tina Widjaja (Public Health and Preventive Medicine Archive, 2020)
Background and purpose: Anxiety is generally found in primary health care patients with physical problems and are often not treated. This condition can affect the patient’s sleep quality. The aim of this study was to determine the relationship between anxiety and sleep quality in patients attending Kecamatan Penjaringan Public Health Center (PHC), North Jakarta. Methods: This is a cross-sectional study of 434 patients attending the health care service of Kecamatan Penjaringan PHC, North Jakarta from August to October 2019. Data was collected with demographic and drug consumption questionnaire, Zung Selfrating Anxiety Scale (SAS) and Pittsburgh Sleep Quality Index (PSQI). Data analysis were including univariate and bivariate analysis conducted with SPSS 25.0. Results: There were 434 respondents aged 17-81 years old involved in the study, with an average age of 47.1 years, 72.4% of them were female, 56.2% with basic education, 54.8% were unemployed and 61.1% with low-income level. As high as 26.3% of the respondents were fallen into anxiety classification, including 19.4% mild anxiety, 5.5% moderate anxiety and 1.4% severe anxiety; while 53.5% of them reported poor sleep quality. Bivariate analysis showed a significant relationship between anxiety and sleep quality in patients attending Kecamatan Penjaringan PHC, North Jakarta (P<0.001). Patients with anxiety were 7.8 times (OR=7.819, 95%CI: 4.462-13.703) more likely to experience poor sleep quality than those without anxiety. Conclusion: There is a significant relationship between anxiety and sleep quality in patients attending Kecamatan Penjaringan PHC, North Jakarta. Detection of anxiety disorders and sleep quality should be considered as one essential part of patients’ care at PHC.